Peningkatan Keterampilan Dasar Mengajar Guru Melalui Scientific Model Supervision Directive Approach - Lumbanbatu, Johannes Sohirimon; Sihotang, Din Oloan (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2022)
One of the goals of teacher supervision is to improve skills and competencies in classroom learning. So that the purpose of this study is to find out how to improve the basic skills of teaching productive teachers of  Vocational High School Arina through the application of scientific  model supervision with a directive approach. The subjects of this study were 5 (five) productive teachers. The research design used was school action research which was carried out in two cycles. The results showed an increase in each skill from cycle I with an average value of 71 with a sufficient value category to an average score of 87 in the second cycle with a good score category. Thus this action research shows that the application of scientific model supervision with a directive approach can improve the basic skills of teaching productive teachers at Vocational High School Arina Sidikalang.